DDEL-10. A NANOPARTICLE PLATFORM FOR INTRATHECAL DELIVERY OF THE HISTONE DEACETYLASE INHIBITOR (HDACi) PANOBINOSTAT IN METASTATIC OR RECURRENT MEDULLOBLASTOMA. (4th December 2020) - Chaudhuri, Sauradip; Mohammad, Afroz S; Zhang, Wenqui; Baker, Cassandra; Broughton, Colton W; Fowler, Martha J; Stabenfeldt, Sarah E; Wechsler-Reya, Robert J; Sandberg, David I; Elmquist, William F; Sirianni, Rachael W
Abstract: INTRODUCTION: Panobinostat is a histone deacetylase inhibitor (HDACi) that is a clinical candidate for treatment of pediatric medulloblastoma and diffuse intrinsic pontine glioma. Panobinostat is poorly water-soluble and experiences a number of barriers to effective delivery. Here, we developed a novel drug delivery system consisting of β-cyclodextrin-poly(β-amino ester). These cyclodextrin-networks (CDNs) self-assemble into nanoparticles encapsulating a high quantity of HDACi for slow release. We sought to test the hypothesis that panobinostat-loaded CDNs would demonstrate a differentiated pharmacokinetic profile compared to free panobinostat in mice after direct administration to cerebrospinal fluid. METHODS: CDNs were synthesized via Michael addition and engineered to encapsulate a library of HDACi drugs. Nanoparticles were characterized for size, surface charge, loading, controlled release, and stability. CDNs or fluorescent surrogate nanoparticles were administered to the cisterna magna of mice. Tissues were collected for LC-MS/MS (pharmacokinetics [PK]: 1, 4, 8, 24, and 48 hrs) or microscopy (localization: 2, 6, 24, and 48 hrs, 1 and 3 wks). RESULTS: Intravital and confocal microscopy demonstrate that nanoparticles distribute rapidly in subarachnoid space and can localize with metastases, persisting for > 3 weeks. Nanoparticle panobinostat is released over weeks and is better tolerated than free drug. CDN-panobinostat delivery tended to be higher in the cerebellum and lower in the spinal cord at both early and late time points compared to freely administered drug. CONCLUSIONS: We present a nanoparticle platform for HDACi delivery with a differentiated PK profile in the CSF compared to free drug. Additional PK and therapeutic studies are ongoing.